Laparoscopic hyperthermic isolated limb perfusion a new minimally invasive approach for HILP. (3rd October 2017) - Solari, N.; Sucameli, F.; Gipponi, M.; De Cian, F.; Cafiero, F.
Abstract: Background: Hyperthermic isolated limb perfusion (HILP) represents a limb-sparing treatment for unresectable soft tissue sarcoma (STS) of the extremities with substantial complete response rates. HILP often provides good functional limb preservation, hence a significant improvement also in terms of quality of life of the patient. Notwithstanding these clear advantages, the traditional technique is still hindered by relatively high post-operative morbidity. Method: We treated a 78-year-old female with unresectable angiosarcoma of the left leg using a new surgical approach: an entirely laparoscopic HILP. Results: No conversion from laparoscopic to "open" surgery was necessary. Since no abdominal muscle section was performed, post-operative pain was low and easily manageable; early mobilisation and early discharge were achieved. Patient developed moderate toxicity, which resolved spontaneously within 3–4 weeks, with complete return to normal daily activities after 30 d. Complete clinical response with preservation of leg function was obtained. Conclusions: We describe for the first time an entirely laparoscopic HILP. Demonstration of this technique's efficacy and safety on a large series of patients is clearly necessary but its therapeutic efficacy appears to be comparable to the standard technique. Furthermore, laparoscopic HILP has shown low post-operative morbidity: no wound complications, mild and easily manageable post-operative pain and early discharge from the hospital and early resuming of daily activities.